Differences in oncological and toxicity outcomes between programmed cell death-1 and programmed cell death ligand-1 inhibitors in metastatic renal cell carcinoma: A systematic review and meta-analysis. (September 2021) - Mori, Keiichiro; Pradere, Benjamin; Quhal, Fahad; Katayama, Satoshi; Mostafaei, Hadi; Laukhtina, Ekaterina; Schuettfort, Victor M.; D'Andrea, David; Egawa, Shin; Bensalah, Karim; Schmidinger, Manuela; Powles, Thomas; et al.
Highlights: Dissimilarities exist between anti-PD-1 and anti-PD-L1 inhibitors. Anti-PD-1 combination therapies exhibited superior oncologic benefits in mRCC. Anti-PD-L1 agents were superior to anti-PD-1 agents in their safety profiles. These differences are vital for future combination therapy trials in mRCC. In network meta-analyses, pembrolizumab plus lenvatinib was the worst tolerated. Abstract: Background: The programmed cell death ligand-1 (PD-L1)/programmed cell death-1 (PD-1) pathway is important in metastatic renal cell carcinoma (mRCC). However, some dissimilarities between anti-PD-1 and anti-PD-L1 inhibitors have emerged. We aimed to assess differences between anti-PD-1 and anti-PD-L1 combination immunotherapies as first-line treatments in mRCC patients. Methods: Multiple databases (PubMed, Web of Science, and Scopus) were searched for articles published until March 2021. Studies were eligible if they compared overall survival (OS), progression-free survival (PFS), objective response rates (ORR), complete response rates (CRR), and adverse events. Results: Five studies met the eligibility criteria. PD-1 combination therapy was associated with significantly better OS and PFS and higher ORR and CRR than sunitinib (hazard ratio [HR]: 0.60, 95% confidence interval [CI]: 0.40–0.89; HR: 0.52, 95% CI: 0.37–0.75; odds ratio [OR]: 3.20, 95% CI: 2.18–4.68; and OR: 3.05, 95% CI: 2.13–4.37, respectively; P < 0.001). For all oncological outcomes, anti-PD-1 agents were superior to anti-PD-L1 agents based on HR and OR (OS: HR = 0.88, PFS: HR = 0.76, ORR: OR = 1.85, and CRR: OR = 2.24). Conversely, anti-PD-L1 agents were superior to anti-PD-1 agents in their safety profiles. In network meta-analyses, pembrolizumab plus lenvatinib seemed the worst tolerated anti-PD-1 combination therapy. Conclusions: Our analysis indicates the superior oncologic benefits of first-line anti-PD-1 combination therapies over anti-PD-L1 combination therapies in mRCC patients. This biological difference is of vital importance for clinical treatment decision making and the design of future rational combination therapy trials in mRCC.